2020
DOI: 10.1021/acscatal.0c00144
|View full text |Cite
|
Sign up to set email alerts
|

Critical Hydrogen Coverage Effect on the Hydrogenation of Ethylene Catalyzed by δ-MoC(001): An Ab Initio Thermodynamic and Kinetic Study

Abstract: The molecular mechanism of ethylene (C 2 H 4 ) hydrogenation on a δ-MoC (001) surface has been studied by periodic density functional theory methods. Activation energy barriers and elementary reaction rates have been calculated as a function of the hydrogen surface coverage, θ H , with relevant properties derived from ab initio thermodynamics and kinetic rate estimates. The hydrogen coverage has a very strong effect on the adsorption energy and the second hydrogenation step of ethylene. A relatively low energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…Titanium carbide, a typical transition metal carbide, has been applied in cutting tools, 1 hard coatings, 2,3 grain inhibitors 4 as well as a catalyst [5][6][7] for years. It is not only due to its desirable physical properties such as high hardness, high melting points, low density and corrosion resistance but also the chemical stability and low thermal expansion coefficient draw huge attention in manufacturing industries.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium carbide, a typical transition metal carbide, has been applied in cutting tools, 1 hard coatings, 2,3 grain inhibitors 4 as well as a catalyst [5][6][7] for years. It is not only due to its desirable physical properties such as high hardness, high melting points, low density and corrosion resistance but also the chemical stability and low thermal expansion coefficient draw huge attention in manufacturing industries.…”
Section: Introductionmentioning
confidence: 99%
“…One of the modern trends in the field of catalysis is the search for a replacement for noble metal catalysts, and metal carbides, especially molybdenum carbides, are extensively studied in this context. [78,79] Recently, carbides have been studied for the first time in hydrogenation with p-H 2 as well -it was shown that Mo 2 C catalysts can provide selectivities to the hydrogen pairwise addition route comparable to those of supported metal catalysts. [80] After a comprehensive characterization and performance comparison of two differently prepared Mo 2 C catalysts, the authors came to the conclusion that the presence of hexagonal-close-packed phase of Mo 2 C in these catalysts is crucial for the enhanced degree of the pairwise addition.…”
Section: Bulk Metal Catalysts Metal Oxides and Carbidesmentioning
confidence: 99%
“…One of the modern trends in the field of catalysis is the search for a replacement for noble metal catalysts, and metal carbides, especially molybdenum carbides, are extensively studied in this context [78,79] . Recently, carbides have been studied for the first time in hydrogenation with p ‐H 2 as well – it was shown that Mo 2 C catalysts can provide selectivities to the hydrogen pairwise addition route comparable to those of supported metal catalysts [80] .…”
Section: Heterogeneous Phipmentioning
confidence: 99%
“…The use of slab models, given their possibilities, accessibility, and moderate computational expenses, has become the de facto workhorse in the last two decades; particularly when modeling reactivity at high coverage regimes of the clean surfaces, [68][69][70] although lately the increased computational resources allowed studying situations at a low coverage, [71][72][73] and including also surface defects such as vacancies, [74][75][76] subsurface species, [77][78][79] surface atoms, [80][81][82] and so on. Notice that slab models also permit to represent regular defects, such as surface steps, see Figure 2(a), by using vicinal surfaces slab models, [83][84][85] allowing also chemical resolution studies on chiral surfaces.…”
Section: Exemplary Modelsmentioning
confidence: 99%